PERSEPSI KEADILAN ORGANISASI DENGAN KESEJAHTERAAN PSIKOLOGIS DI TEMPAT KERJA PADA PERAWAT - Yulistiani Yulistiani; Listya Istiningtyas; Muhamad Uyun (Psikis : Jurnal Psikologi Islami, 2018)
This study aims to determine the relationship between perception of organizational justice to psychological welfare in the workplace in nursing. The population numbered 120, and a sample of 97 people were drawn based on a sampling technique with Cohen Manion and Morrison tables. Data were collected using organizational justice perception scale based on organizational justice perception dimension according to Robin & Judge. As well as the scale of psychological welfare based on the dimensions of psychological welfare according to the psychological welfare dimensions of Ryff and Keyes. The analytical method used is a simple regression analysis that shows the R value of 0.929 with the value R2 = 0.863, with p = 0,000 where p <0.05. So the hypothesis proved that there is a significant relationship between Perception of Organizational Justice with Psychological Welfare at Nurse. The researcher suggests for further researchers to use different research methods to enrich information and knowledge as well as better and more detailed results.